Incidence and Risk Factors of Diabetic Foot Ulcer: A Population-Based Diabetic Foot Cohort (ADFC Study)—Two-Year Follow-Up Study - Leila Yazdanpanah; Hajieh Shahbazian; Iraj Nazari; Hamid Reza Arti; Fatemeh Ahmadi; Seyed Ehsan Mohammadianinejad; Bahman Cheraghian; Saeed Hesam (International Journal of Endocrinology)
Aim/Introduction. This study was carried out to assess the incidence and risk factors of diabetic foot ulcer (DFU). Materials and Methods. In this prospective cohort study in a university hospital, all the participants were examined and followed up for new DFU as final outcome for two years. To analyze the data, the variables were first evaluated with a univariate analysis. Then variables with P value < 0.2 were tested with a multivariate analysis, using backward-elimination multiple logistic regression. Results. Among 605 patients, 39 cases had DFU, so we followed up the remaining 566 patients without any present or history of DFU. A two-year cumulative incidence of diabetic foot ulcer was 5.62% (95% CI 3.89–8.02). After analysis, previous history of DFU or amputation [OR = 9.65, 95% CI (2.13–43.78), P value = 0.003], insulin usage [OR = 5.78, 95% CI (2.37–14.07), P value < 0.01], gender [OR = 3.23, 95% CI (1.33–7.83), P value = 0.01], distal neuropathy [OR = 3.37, 95% CI (1.40–8.09), P value = 0.007], and foot deformity [OR = 3.02, 95% CI (1.10–8.29), P value = 0.032] had a statistically significant relationship with DFU incidence. Conclusion. Our data showed that the average annual DFU incidence is about 2.8%. Independent risk factors of DFU development were previous history of DFU or amputation, insulin consumption, gender, distal neuropathy, and foot deformity. These findings provide support for a multifactorial etiology for DFU.